Coreduction methodology for immiscible alloys of CuRu solid-solution nanoparticles with high thermal stability and versatile exhaust purification ability. Issue 42 (25th September 2020) - Huang, Bo; Kobayashi, Hirokazu; Yamamoto, Tomokazu; Matsumura, Syo; Nishida, Yoshihide; Sato, Katsutoshi; Nagaoka, Katsutoshi; Haneda, Masaaki; Kawaguchi, Shogo; Kubota, Yoshiki; Kitagawa, Hiroshi
Abstract : This study provides a coreduction methodology for solid solution formation in immiscible systems, with an example of a whole-region immiscible Cu–Ru system. Abstract : This study provides a coreduction methodology for solid solution formation in immiscible systems, with an example of a whole-region immiscible Cu–Ru system. Although the binary Cu–Ru alloy system is very unstable in the bulk state, the atomic-level well-mixed CuRu solid solution nanoparticles were found to have high thermal stability up to at least 773 K in a vacuum. The exhaust purification activity of the CuRu solid solution was comparable to that of face-centred cubic Ru nanoparticles. According to in situ infrared measurements, stronger NO adsorption and higher intrinsic reactivity of the Ru site on the CuRu surface than that of a pure Ru surface were found, affected by atomic-level Cu substitution. Furthermore, CuRu solid solution was a versatile catalyst for purification of all exhaust gases at a stoichiometric oxygen concentration.